What drives the relationship between bank and sovereign credit risk? - Isabel Schnabel; Ulrich Schüwer (Sachverständigenrat zur Begutachtung der Gesamtwirtschaftlichen Entwicklung, 2016)
The positive relationship between bank and sovereign credit risk in the Eurozone, the so-called sovereign-bank nexus, is seen as a major threat for the stability of the Eurozone. This paper explores potential bank-level and country-level drivers of this relationship. We find that banks' home bias in their sovereign exposures and their low equity ratios as well as countries' high debt-to-GDP ratios and low perceived government effectiveness are positively related to the sovereign-bank nexus. While these results do not necessarily reflect causal relationships, they suggest that promoting banks' diversification of sovereign exposures could be an effective measure to mitigate the sovereign-bank nexus.
Keywords: G21; G28; 330; sovereign-bank nexus; home bias; sovereign exposures; CDS spreads